2018
DOI: 10.1016/j.jevs.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Plugged Ampullae in a Donkey Stallion ( Equus asinus )

Abstract: The donkey jack sex glands are larger than stallions, responsible for producing most part of seminal plasma and the second fraction of ejaculate, along with epididymis tail. Plugged ampullae occur by sperm accumulation obstructing the lumen, inducing decrease in sperm quality and may cause azoospermia. In this study, a Pêga breed donkey jack, aging 4 years, was evaluated for breeding soundness evaluation due to a sudden decrease in semen parameters and low fertility rates. Palpation, measurements, and ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Additionally, azoospermia stages have been described in donkeys due to plugged ampullae causing total ampullae obstruction (Segabinazzi et al 2018) or after immunocastration procedures (Rocha et al 2018), but also may be physiologically mediated by undifferentiated embryonic cell transcription factor 1 (UTF 1) and deleted in azoospermia-like (DAZL) expression in donkey testis (Lee et al 2017;Choi et al 2020) and has been suggested to be an effect derived from ageing (Liu et al 2021) which was supported by our results as shown in Figure 3. Figure 8 also describe a decrease in total spermatozoa motility which is concomitant with the azoospermia stage detected in Figure 3.…”
Section: Doradosupporting
confidence: 84%
“…Additionally, azoospermia stages have been described in donkeys due to plugged ampullae causing total ampullae obstruction (Segabinazzi et al 2018) or after immunocastration procedures (Rocha et al 2018), but also may be physiologically mediated by undifferentiated embryonic cell transcription factor 1 (UTF 1) and deleted in azoospermia-like (DAZL) expression in donkey testis (Lee et al 2017;Choi et al 2020) and has been suggested to be an effect derived from ageing (Liu et al 2021) which was supported by our results as shown in Figure 3. Figure 8 also describe a decrease in total spermatozoa motility which is concomitant with the azoospermia stage detected in Figure 3.…”
Section: Doradosupporting
confidence: 84%
“…Stallions are frequently affected with ampullary blockage; however, surprisingly there is only one report of ampullary blockage in a four-year-old jack. This jack was reported to respond to standard stallion treatment with oxytocin and transrectal massage coupled with frequent semen collections 50 While all four accessory sex glands contribute to the seminal plasma in jacks, their specific contributions remain to be determined. Apart from the vesicular glands, all the other glands are larger in jacks than stallions 30,51 .…”
Section: Functional and Reproductive Anatomy And Physiology Of Donkey...mentioning
confidence: 99%
“…Over the past 10 years, there has been increase in studies in the field of donkey reproduction, with the aim of preserving this breed and enhancing fertility. Ultrasonography could provide information about the male genital tract to aid in the detection of genital abnormalities (Gacem et al., 2020; Segabinazzi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%